Stres in spoprijemanje z njim pri študentih Univerze v Ljubljani - Videmšek, Naja (Šport (Ljubljana), 2019)
The aim of the study was to analyse the stress and stress coping among 750 students of six faculties of the University of Ljubljana. The data were processed with the SPSS. We calculated the basic statistics, the hypotheses were tested by using a Chi-square test at the significance level of 5% (p <- 0.05). The results of the study showed that stress occurs occasionally among most of the students (46.8%), often among 30.4% of the students, and every day among 4.7% of the students. The students of the Faculty of Medicine are more affected by stress than other students, especially the students of the Faculty of Sport. Women suffer more from stress than men. 82.2% of the students cited as the reason for the tension, stress and a feeling of heaviness burden of study. Among them, most students are from the Faculty of Medicine and at least students of the Faculty of Sport, and most of them were women. The students of the Faculty of Mechanical Engineering and the Faculty of Medicine learn continuously. Outside the examination period, 38.5% of students sleep only 5 to 6 hours per day. Only 12.8% of students can easily handle stress, 70% of them handle stress with some effort and 16.5% of them with great effort; among them, students of the third year and men cope better with stress than others. As a stress coping strategy, a large majority (72%) of students mentions sports activity, mostly students of the Faculty of Sport and at least students of the Faculty of Education. Only 5.2% of students do not even deal with sports, most of them are active in sports from 3 to 5 days a week, from 30 to 60 minutes. Our recommendation is that students should be encouraged to continue sports participation and should also be regularly informed of other stress coping strategies.
Keywords: spoprijemanje s stresom; stres; stress; stress coping; students; študenti; University of Ljubljana; Univerza v Ljubljani